High‐resolution 1H‐MRSI of the brain using SPICE: Data acquisition and image reconstruction. Issue 4 (14th September 2016) - Lam, Fan; Ma, Chao; Clifford, Bryan; Johnson, Curtis L.; Liang, Zhi‐Pei
Abstract : Purpose: To develop data acquisition and image reconstruction methods to enable high‐resolution 1 H MR spectroscopic imaging (MRSI) of the brain, using the recently proposed subspace‐based spectroscopic imaging framework called SPICE (SPectroscopic Imaging by exploiting spatiospectral CorrElation). Theory and Methods: SPICE is characterized by the use of a subspace model for both data acquisition and image reconstruction. For data acquisition, we propose a novel spatiospectral encoding scheme that provides hybrid data sets for determining the subspace structure and for image reconstruction using the subspace model. More specifically, we use a hybrid chemical shift imaging /echo‐planar spectroscopic imaging sequence for two‐dimensional (2D) MRSI and a dual‐density, dual‐speed echo‐planar spectroscopic imaging sequence for three‐dimensional (3D) MRSI. For image reconstruction, we propose a method that can determine the subspace structure and the high‐resolution spatiospectral reconstruction from the hybrid data sets generated by the proposed sequences, incorporating field inhomogeneity correction and edge‐preserving regularization. Results: Phantom and in vivo brain experiments were performed to evaluate the performance of the proposed method. For 2D MRSI experiments, SPICE is able to produce high‐SNR spatiospectral distributions with an approximately 3 mm nominal in‐plane resolution from a 10‐min acquisition. For 3D MRSI experiments, SPICE is able to achieve an approximately 3 mm in‐plane and 4 mm through‐plane resolution in about 25 min. Conclusion: Special data acquisition and reconstruction methods have been developed for high‐resolution 1 H‐MRSI of the brain using SPICE. Using these methods, SPICE is able to produce spatiospectral distributions of 1 H metabolites in the brain with high spatial resolution, while maintaining a good SNR. These capabilities should prove useful for practical applications of SPICE. Magn Reson Med 76:1059–1070, 2016. © 2015 Wiley Periodicals, Inc.